Membuka Cakrawala Pendidikan dan Mengatasi Tantangan Global Melalui Wawasan Pendidikan - Gustina, Mila (Indonesian Journal Publisher, 2024)
This article discusses the importance of opening educational horizons to address global challenges through inclusive, relevant and sustainable educational insights. Challenges such as technological developments and globalization, the focus on access to education, and the relevance of education to the needs of the world of work are described as crucial factors that need to be addressed. This paper provides an overview of the importance of broad access to education, technology integration, collaboration with world industry, and efforts to achieve gender equality. By paying attention to these aspects, education can play a key role in facing global challenges and preparing future generations for a better future.